Impact of Ridomil, Bavistin and Agrothoate on arbuscular mycorrhizal fungal colonization, biochemical changes and potassium content of cucumber plants - Rabab, A Metwally (Ecotoxicology (London, England), 2019)
The effect of pesticides on arbuscular mycorrhizal (AM) fungi and plants are of interest to agriculture. Hence, the present study was conducted to understand the potential effect of two systemic fungicides (Ridomil "250 and 500 mg/L" and Bavistin "500 and 1000 mg/L") and one insecticide (Agrothoate 40% EC "1.25 and 2.50 ml/L H2O") on AM fungal colonization, some biochemical changes and K+ content of cucumber plants (Cucumis sativus L.). AM and non-AM cucumber plants were exposed to two concentrations of each pesticide. Results revealed an increase in mycorrhizal colonization (F%) with Ridomil and Bavistin applications however there was a decrease in this percentage with Agrothoate. Stimulation of phosphatase enzymes activity was observed subsequent to pesticides application. Moreover, there was a significant decrease in K+ content with increasing pesticides concentration, and this decrease was more distinct in non-AM cucumber plants than AM ones. Our results also showed a significant increase in malondialdehyde (MDA) content in all pesticides treated cucumber plants relative to control ones. Thus, the content of non-enzymatic antioxidants such as phenolic and flavonoids was stimulated by pesticides application and with AM fungal inoculation, further augmentation in their contents was detected. Therefore AM fungi can partially or completely alleviate pesticides toxicity and helpful to overcome some of their negative effects on the biochemical metabolites of cucumber. Thus the judicious use of these pesticides may have stimulatory effect on AM fungal colonization